Lignocellulosic biomass carbonization for biochar production and characterization of biochar reactivity. (April 2022) - Qin, Fanzhi; Zhang, Chen; Zeng, Guangming; Huang, Danlian; Tan, Xiaofei; Duan, Abing
Abstract: Lignocellulosic biomass (LB) pyrolysis and gasification technologies for bio-oil, syngas and process heat have been widely described, and biochar, as a significant byproduct of LB pyrolysis, has also received increasing attention because of it global sustainability. Biochar is attractive to researchers, mainly due to the value of its activity and reactivity, bringing the possibility of achieving carbon utilization and carbon neutralization. However, few studies have systematically described the changes in chemical composition and structure of LB during its carbonization process, as well as the origin of produced biochar's reactivity. A better understanding of what chemical substances have facilitated biochar reactivity and how they function is needed, which is of great value for environmental remediation analysis and green application strategy formulation. Herein, the new insights into the possible decomposition/transformation mechanisms of LB to functionalized biochar were discussed. Subsequently, the basic structure of lignocellulosic biomass derived biochar (LBC) was studied, and its reactivity-related compositions were also summarized. More importantly, discussion was expanded on the origin of LBC's reactivity and the reactivity expression ways. And the outlook section will highlight insights into future directions and prospects, aiming to overcome current limitations by developing more methods and exploring other green applications. Graphical abstract: Image 1 Highlights: The progresses and challenges of LBC conversion technologies were discussed. The possible transformation mechanisms from LB to LBC was revealed. The changes of reactivity-related characteristics in LBC production were reviewed. New insights into the origin of LBC surface reactivity were developed. The reactivity expression ways of LBC were summarized.